2010
DOI: 10.1586/erp.10.69
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacoeconomics of voriconazole in the management of invasive fungal infections

Abstract: The incidence of invasive fungal infection has risen in recent years with the introduction of more intensive chemotherapy regimens and the advent of stem cell and solid-organ transplants. In patients undergoing chemotherapy, mortality rates ranging from 50 to 90% have been associated with documented invasive fungal infection. Voriconazole is a second-generation triazole, which is a synthesized derivative of fluconazole. It was first approved for marketing in the USA in 2002. Voriconazole has excellent bioavail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
3
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 77 publications
1
3
0
Order By: Relevance
“…Their data suggest nonlinear corneal absorption of voriconazole, which is consistent with the results of our previous studies that showed that the penetration of voriconazole via an intact cornea is unlikely to be concentration dependent for a concentration range between 1% and 2% (5, 6). The ocular kinetics of topical voriconazole seem to reflect the nonlinearity of the voriconazole pharmacokinetics profile when administered systemically (10). In addition, our results show a slower decline in voriconazole aqueous humor concentrations than was previously reported (elimination t 1/2 ϭ 0.82 h) by Senthilkumari et al (8), who adopted a one-compartment model.…”
supporting
confidence: 68%
“…Their data suggest nonlinear corneal absorption of voriconazole, which is consistent with the results of our previous studies that showed that the penetration of voriconazole via an intact cornea is unlikely to be concentration dependent for a concentration range between 1% and 2% (5, 6). The ocular kinetics of topical voriconazole seem to reflect the nonlinearity of the voriconazole pharmacokinetics profile when administered systemically (10). In addition, our results show a slower decline in voriconazole aqueous humor concentrations than was previously reported (elimination t 1/2 ϭ 0.82 h) by Senthilkumari et al (8), who adopted a one-compartment model.…”
supporting
confidence: 68%
“…No prior studies have compared the cost-effectiveness of isavuconazole vs. voriconazole in the treatment of IA; however, there are multiple studies comparing voriconazole to other IA treatments [13, 38]. Those studies have concluded that voriconazole is the preferred therapy for IA in terms of cost-effectiveness.…”
Section: Discussionmentioning
confidence: 99%
“…Fusarium species possesses several virulence factors, including the production of tricothecene and other mycotoxins. These mycotoxins can suppress humoral and cellular immunity, and cause break down of tissue [ 4 ]. Such skin breakdown may precede infection by up to one year [ 2 ].…”
mentioning
confidence: 99%
“…If Fusarium species are identified in culture or biopsy, aggressive debridement should be performed and antifungal therapy should be administered. Previous guidelines recommended amphotericin B for treatment of fungal infections, including Fusarium infection, however, in a recent analysis, voriconazole was recommended as the most cost-effective therapy [ 4 ]. Treatment of cutaneous fusariosis is usually successful.…”
mentioning
confidence: 99%